Extending the role of nursing assistants in mental health inpatient settings: A multi‐method study. (19th March 2021) - Roche, Michael A.; Glover, Suzanne; Luo, Xiaoou; Joyce, Mark; Rossiter, Chris
Abstract: With continued growth in the demand for nursing care, many organizations have incorporated nursing assistants into the acute care workforce. However, role descriptions are often generic and do not provide clarity in specialist areas such as mental health inpatient settings. Issues have been noted regarding the role of assistants, delegation, and their integration with the nursing team. This study extended an existing set of care activities and explored the perceptions of nursing assistants and registered nurses regarding these activities. A modified Delphi approach added 14 new care activities for nursing assistants. A follow‐up survey found significant differences between nursing assistants and registered nurses regarding utilization of the activities, delegation, teamwork, and role clarity. Future research must incorporate the perspectives of those with lived experience of mental health issues, and develop an understanding of the interactions between nursing assistant care activities and other factors such as local supports, skillmix, and the practice environment, as these may impact how an organization can introduce nursing assistants to specialty areas while maintaining consumer and staff safety.